1999
DOI: 10.1183/09031936.99.13614069
|View full text |Cite
|
Sign up to set email alerts
|

Nasal and lower airway level of nitric oxide in children with primary ciliary dyskinesia

Abstract: The aim of this study was to compare exhaled nitric oxide concentrations obtained during controlled slow exhalation, presently considered as the method of choice, with two sampling methods that are easily performed by children: blowing air into a balloon and tidal breathing through a mouthpiece.One hundred and one well controlled, stable allergic asthmatic children (median age 11.7 yrs) performed the following tasks in duplicate: 1) exhalation from total lung capacity through a mouthpiece against a resistor wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(107 citation statements)
references
References 30 publications
10
93
0
4
Order By: Relevance
“…A high or normal nasal NO level can help to exclude PCD, particularly in those in whom the history is not classical, but it should be noted that a few patients with PCD may have levels within the normal range [64]. A low measurement is not diagnostic of PCD, with low levels occurring in other conditions, including CF, panbronchiolitis, nasal blockage and nasal polyposis.…”
Section: Screening Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…A high or normal nasal NO level can help to exclude PCD, particularly in those in whom the history is not classical, but it should be noted that a few patients with PCD may have levels within the normal range [64]. A low measurement is not diagnostic of PCD, with low levels occurring in other conditions, including CF, panbronchiolitis, nasal blockage and nasal polyposis.…”
Section: Screening Testsmentioning
confidence: 99%
“…Nasal nitric oxide measurement A number of studies have shown that levels of exhaled nitric oxide, and particularly nasal NO, are very low in PCD [9,51,64,65]. A high or normal nasal NO level can help to exclude PCD, particularly in those in whom the history is not classical, but it should be noted that a few patients with PCD may have levels within the normal range [64].…”
Section: Screening Testsmentioning
confidence: 99%
“…21 Measured nNO concentration was multiplied by sampling fl ow to determine nNO production in nanoliters per minute. For velum closure nNO and tidal breathing nNO, values , 77 nL/min 20,22,23 and , 40 nL/min, 21,24 respectively, were considered low and within PCD range. Velum closure nNO measurements were also collected from 77 healthy pediatric control participants.…”
Section: For Editorial Comment See Page 1136mentioning
confidence: 99%
“…All cases were confirmed by a low concentration of nitric oxide (NO) measured in exhaled air. 19 NO was measured from the nasal cavity by a chemiluminescence analyzer with a threshold value of 200 ppb for diagnosing PCD. In 60% of the families, the clinical diagnosis was confirmed by transmission electron microscopy analysis of bronchial cilia ultrastructure; the analysis revealed defects of outer or outer and inner dynein arms; a representative EM picture is shown in Supplementary Figure 1.…”
Section: Methodsmentioning
confidence: 99%